Conservation prioritization in the context of uncertainty. (August 2015) - Collen, B.
<x xml:space="preserve">Abstract</x> Read the Feature Paper: Setting evolutionary‐based conservation priorities for a phylogenetically data‐poor taxonomic group (Scleractinia); other Commentaries on this paper: Valuing species on the cheap; Regional specific approach is a next step for setting evolutionary‐based conservation priorities in the scleractinian corals and the Response from the authors: Setting evolutionary based conservation priorities for a phylogenetically data‐poor taxonomic group (Scleractinia): response to the commentaries